Extensively Drug-Resistant Klebsiella pneumoniae Causing Nosocomial Bloodstream Infections in China: Molecular Investigation of Antibiotic Resistance Determinants, Informing Therapy, and Clinical Outcomes - Bi, Wenzi; Liu, Haiyang; Dunstan, Rhys A.; Li, Bin; Torres, Von Vergel L.; Cao, Jianming; Chen, Lijiang; Wilksch, Jonathan J.; Strugnell, Richard A.; Lithgow, Trevor; Zhou, Tieli (Frontiers in Microbiology, 2017)
The rise in diversity of antimicrobial resistance phenotypes seen in Klebsiella pneumoniae is becoming a serious antibiotic management problem. We sought to investigate the molecular characteristics and clinical implications of extensively drug-resistant (XDR) K. pneumoniae isolated from different nosocomial bloodstream infections (BSIs) patients from July 2013 to November 2015. Even in combination treatment, meropenem did not protect against mortality of BSIs patients (P=0.015). In contrast, tigecycline in combination with other antimicrobial agents significantly protected against mortality (P=0.016). Antimicrobial susceptibility tests, molecular detection of antibiotic resistance determinants, conjugation experiments, multilocus sequence typing (MLST), S1-PFGE, Southern blot, SDS-PAGE, immunoblot analysis and pulsed-field gel electrophoresis (PFGE) were used to characterize these isolates. These XDR K. pneumoniae strains were resistant to conventional antimicrobials except tigecycline and polymyxin B and co-harbored diverse resistance determinants. rmtB, blaKPC-2 as well as blaCTX-M-9 were located on a transferable plasmid of ~54.2 kb and the most predominant replicon type was IncF. 23 of the 35 isolates belonging the predominant clone were found to incorporate the globally-disseminated sequence type ST11, but others including a unique, previously undiscovered lineage ST2281 (allelic profile: 4-1-1-22-7-4-35) were also found and characterized. The porins OmpK35 and OmpK36 were deficient in two carbapenemase-negative carbapenem-resistant strains, suggesting decreased drug uptake as a mechanism for carbapenem resistance. This study highlights the importance of tracking hospital acquired infections, monitoring modes of antibiotic resistance to improve health outcomes of BSIs patients and to highlight the problems of XDR K. pneumoniae dissemination in healthcare settings.